Association of the resolvin precursor 17-HDHA, but not D- or E- series resolvins, with heat pain sensitivity and osteoarthritis pain in humans - Valdes, Ana M.; Ravipati, Srinivasarao; Menni, Cristina; Abhishek, Abhishek; Metrustry, Sarah; Harris, Juliette; Nessa, Ayrun; Williams, Frances M.K.; Spector, Tim D.; Doherty, Michael; Chapman, Victoria; Barrett, David A. (Nature Publishing Group, 2017)
Resolvins are omega-3 fatty acid derived potent bioactive lipids that resolve inflammation and modulate transient receptor potential channels. Exogenous administration of the resolvin precursor 17-HDHA shows a strong analgesic effect in animal models of osteoarthritis and acute inflammatory pain, but has not been studied in humans. Our aim was to assess the role of 17-HDHA and resolvins in heat pain sensitivity and in osteoarthritis pain in humans. Resolvins D1, D2, D3, D5, E1 and 17-HDHA, were measured by liquid chromatography-mass spectrometry and tested for association with heat pain thresholds in 250 healthy volunteers who had undergone quantitative sensory testing. Resolvins D1, D2 and 17-HDHA were then tested in 62 individuals affected with knee osteoarthritis and 52 age matched controls and tested for association with knee pain. Circulating levels of docosahexaenoic acid (DHA) were also measured. Levels of 17-HDHA, but not those of the other 5 resolvins tested, were associated with increased heat pain thresholds (beta = 0.075; 95%CI 0.024, 0.126; p<0.0046). 17-DHDA was associated with lower pain scores in OA patients (beta -0.41; 95%CI-0.69, -0.12; p<0.005; adjusted for covariates) but not with osteoarthritis. The associations of 17-HDHA associations with heat pain sensitivity and osteoarthritis pain were independent of DHA levels.